Induction therapy pre‐autologous stem cell transplantation in immunoglobulin light chain amyloidosis: a retrospective evaluation. Issue 10 (14th July 2016) - Hwa, Yi L.; Kumar, Shaji K.; Gertz, Morie A.; Lacy, Martha Q.; Buadi, Francis K.; Kourelis, Taxiarchis V.; Gonsalves, Wilson I.; Rajkumar, S. Vincent; Go, Ronald S.; Leung, Nelson; Kapoor, Prashant; Dingli, David; et al.
Abstract : There is no consensus on whether patients with immunoglobulin light chain amyloidosis (AL) should receive induction therapy prior to an autologous stem cell transplant (ASCT). This study investigated the relationships between baseline bone marrow plasmacytosis (BMPC), cardiac staging, and pre‐transplant induction in AL patients. All patients who received ASCT for AL within 12 months of diagnosis were included. Patient characteristics and outcomes were abstracted. Univariate and multivariate modeling was performed. Among 415 AL patients, 35% had induction prior to ASCT. Post‐ASCT hematologic CR plus VGPR rates were significantly higher in those with baseline BMPC ≤ 10% compared to BMPC >10% (58% versus 40%, P = 0.0013). Significant risk factors for lack of attainment of CR included attenuated dose melphalan conditioning, baseline BMPC > 10%, no induction, and male gender. The 5‐year OS for the entire group was 65%. On multivariate analysis, risk factors for inferior OS included no induction therapy, advanced AL amyloid staging, BMPC > 10%, attenuated conditioning melphalan dose, and male gender. Patients with Mayo 2012 stage I–II patients with BMPC ≤ 10%, who comprised 56% of the ASCT population fared exceedingly well regardless of whether or not they received induction therapy with a 5‐year OS of 81 to 83%. Induction therapy pre‐ASCT may improve outcomes among AL patients due to a rapid reduction of toxic light chains or alternatively by elimination of less fit patients by "testing" their ability to tolerate chemotherapy. Prospective studies will be required to sort out these and other questions. Am. J. Hematol. 91:984–988, 2016. © 2016 Wiley Periodicals, Inc.